Perception of the public in Samarahan towards the arising of dengue cases / Nur Syazwani Mohamad and Iliana Shazwanie Sobri - Mohamad, Nur Syazwani; Sobri, Iliana Shazwanie (2014)
This chapter focuses the background of study which is on the public awareness towards the increasing on the arising on the dengue cases. Section 1.1 discusses on the background of study, Section 1.2 explain the problem statement and Section 1.3 states research questions and Section 1.4 on the other hand states the research objectives and Section 1.5 is on the information regarding the scope of study. In addition, Section 1.6 explains the significant of study and lastly Section 1.7 is all about definition of terms and concepts.